Low-power quasi-continuous hybrid volatile/nonvolatile tuning of ring resonators - Jayita Dutta; Rui Chen; Virat Tara; Arka Majumdar (APL Photonics)
Programmable photonic integrated circuits are expected to play an increasingly important role in enabling high-bandwidth optical interconnects and large-scale in-memory computing as needed to support the rise of artificial intelligence and machine learning technology. To that end, chalcogenide-based non-volatile phase-change materials (PCMs) present a promising solution due to zero static power. However, high switching voltage and a small number of operating levels present serious roadblocks to the widespread adoption of PCM-programmable units. Here, we demonstrate an electrically programmable wide bandgap Sb2S3-clad silicon ring resonator using a silicon microheater at a complementary-metal–oxide–semiconductor compatible voltage of <3 V. Our device shows a low switching energy of 35.33 nJ (0.48 mJ) for amorphization (crystallization) and reversible phase transitions with high endurance (>2000 switching events) near 1550 nm. Combining a volatile thermo-optic effect with non-volatile PCMs, we demonstrate 7-bit (127 levels) operation with excellent repeatability and reduced power consumption. Our demonstration of low-voltage and low-energy operation, combined with the hybrid volatile–nonvolatile approach, marks a significant step toward integrating PCM-based programmable units in large-scale optical interconnects.